Biomedical Applications and Bioavailability of Curcumin-An Updated Overview - Soo-In Sohn; Arumugam Priya; Boopathi Balasubramaniam; Pandiyan Muthuramalingam; Chandran Sivasankar; Anthonymuthu Selvaraj; Alaguvel Valliammai; Ravi Jothi; Subramani Pandian (MDPI AG, 2021)
Curcumin, a yellow-colored molecule derived from the rhizome of Curcuma longa, has been identified as the bioactive compound responsible for numerous pharmacological activities of turmeric, including anticancer, antimicrobial, anti-inflammatory, antioxidant, antidiabetic, etc. Nevertheless, the clinical application of curcumin is inadequate due to its low solubility, poor absorption, rapid metabolism and elimination. Advancements in recent research have shown several components and techniques to increase the bioavailability of curcumin. Combining with adjuvants, encapsulating in carriers and formulating in nanoforms, in combination with other bioactive agents, synthetic derivatives and structural analogs of curcumin, have shown increased efficiency and bioavailability, thereby augmenting the range of applications of curcumin. The scope for incorporating biotechnology and nanotechnology in amending the current drawbacks would help in expanding the biomedical applications and clinical efficacy of curcumin. Therefore, in this review, we provide a comprehensive overview of the plethora of therapeutic potentials of curcumin, their drawbacks in efficient clinical applications and the recent advancements in improving curcumin's bioavailability for effective use in various biomedical applications.